Port economics - Talley, Wayne Kenneth (Routledge maritime masters, 2018)
Port Economics is the study of the economic decisions (and their consequences) of the users and providers of port services. A port works as an "engine" for economic development. This book provides a detailed discussion of port freight service users, such as freight water and land carriers, that have their ships and vehicles serviced and their cargoes unloaded by ports, as well as passenger services such as ferry carriers which are serviced by ferry passenger ports. This updated and comprehensive introduction to port economics will be of benefit to students and researchers in their study of port economics and management. It is also of great importance to professionals who manage and operate ports as well as freight and passenger carriers.